En Lixboa sobre lo mar (rio Tejo). A organização e a estruturação do espaço urbano das origens ao século XIV - Carlos Guardado da Silva (Confins)
This qualitative study, based on documentary research, analyzes the evolution and the structuring of the urban space of Lisbon, from its origins until the 14th century, in its close relationship with the river Tagus, at the time designated by a sea near the city. The study stems from the founding of the site of Lisbon, in the 8th century BC, with an Orientalizing matrix, an identity expressed by the Phoenician origin of this place-name, followed by the Romanized city (Olisipo) that, between 19 and 13 BC, received from the emperor Roman Augustus the status of municipium civium Romanorum (Municipality of the Roman citizens), conquered by the Arabs, although the greater contingent was Berber, around 714.In 1147, it was reconquested by the troops of the Portuguese King Afonso I, becoming, after the middle of the 13th century, the capital of the kingdom. Hereafter, the city grew politically, economically and geographically, always in close relation with the river and the sea (which, in this case is also the river), which supported its importance, given its strategic location. This importance dates back to the Islamic period, when maid vessels for navigation on the high seas were built, in a continuous and dynamic maritime activity, specially navigation and other activities related to the sea that were the basis of the development of the city that helps explaining the demographic growth of the region. The study ends with the analysis of the buildings of power - religious, economic and political - as structural as the geographical elements, especially the Tagus river, in the organization of the urban space.